Respon Pertumbuhan Kelapa Sawit (Elaesis guineensis Jacq.) Fase TM 1 Terhadap Pemberian Kompos Tankos Kelapa Sawit dan Asam Humat - Fatimah Az Zahra; Mira Ariyanti; Mochamad Arief Soleh; Cucu Suherman; Santi Rosniawaty (Jurnal Penelitian Kelapa Sawit, 2025)
The excessive use of chemical fertilizers can damage ecosystems and reduce soil fertility, negatively impacting crop production. The addition of organic materials to the soil, such as empty fruit bunch (EFB) compost and humic acid, can mitigate these negative effects. The nutrient content in EFB compost can enhance plant growth, while humic acid can improve nutrient absorption by plants. This study aimed to determine the optimal combination of EFB compost and humic acid doses for achieving the best growth of mature phase oil palm in its first year of production. The research was conducted at the Ciparanje Experimental Farm, Faculty of Agriculture, Universitas Padjadjaran, Jatinangor, from February to June 2024, using a randomized block design (RBD) with four treatments and six replications. The treatments tested were: 2.5 kg/plant of NPKMg fertilizer (12:12:17:2); 50 kg/plant of EFB compost; 30 kg/plant of EFB compost + 300 mL/plant of humic acid; and 10 kg/plant of EFB compost + 300 mL/plant of humic acid. The results showed that, in general, there were no significant differences in most growth parameters observed. Significant differences were only found in the number of fronds, particularly at 2 and 4 weeks after treatment (WAT), with the application of 10 kg/plant of EFB compost + 300 mL/plant of humic acid yielding the best results.